Analisis Penyebab Kecacatan Produk Weight A Handle Menggunakan Metode Fault Tree Analysis dan Failure Mode and Effect Analysis sebagai Rancangan Perbaikan Produk - Yanuar Alfianto (Universitas Bunda Mulia, 2019)
PT. Garuda Metalindo, which is engaged in the manufacturing industry, is currently experiencing a product failure of 2.5% in the production process and this exceeds the failure tolerance set by the company, which amounts to 10 units of 1000 units per process function or about 1% in the production process. Failure tolerance that exceeds the limit so that improvements need to be made to reduce the number of product defects in each production process. This study uses Fault Tree Analysis (FTA) to identify the causes of product defects based on the current production process, the next stage using Failure Mode and Effect Analysis (FMEA) to identify potential failures, modes, potential effects of failure, causes of failure, detection modes, and determine the rating against severity, occurrence, and detection on the risk priority number in the production process. Based on the results of the assessment on the RPN, a cold forming process with a score of 576, surface finishing with a score of 512 was obtained, machining 1 with a score of 441, and machining 2 with a score of 392. Proposed improvements for cold forming defects by monitoring and making checking tools (jigs), defect surface finishing by supervising and making product shelves, machining defects 1 with product inspection and making tools for checking (jig), and replacement of drill bit types, machining defects 2 with lamp and insert replacement and periodic inspection. By applying these proposals it is expected to reduce the level of product disability.